Implementasi Pemimpin Kristen Berhati Hamba Menurut Markus 5:21-43 - Subagyo, Heru; Ngesthi, Yonathan Salmon Efrayim (Pusat Studi Pentakosta Indonesia, 2022)
A leader is a person who gives orders to his followers. To lead means to walk in front, to show the way for followers to follow. This means that the leader is a figure who becomes an example or role model. The concept of Christian leadership is based on the leadership of Jesus. Jesus' leadership style was “servant leadership” and not being served. The purpose of this paper is to make the servant-hearted leadership style a role model for every Christian leader, the figure who becomes the servant-hearted leader is Jairus.This research uses a descriptive literature method, which is to learn about servant-hearted leaders according to Mark 5:21-43. The conclusions that can be conveyed are, first, servant-hearted leadership becomes the lifestyle of every Christian leader. Second, Christian leaders can impart their exemplary ministry style so that it has an impact on the character of the congregation or other God's ministries. Third, it can encourage the emergence of new leaders who have a servant's heart.Pemimpin, adalah orang yang memberi perintah kepada pengikutnya. Memimpin berarti berjalan di depan, menunjukkan jalan agar pengikutnya mengikutnya. Ini artinya pemimpin adalah figur yang menjadi contoh atau teladan. Konsep kepemimpinan kristen berdasar pada kepemimpinan Yesus. Gaya kepemimpinan Yesus adalah “kepemimpinan yang melayani” dan bukan dilayani. Tujuan karya tulis ini agar gaya kepemimpinan berhati hamba menjadi panutan bagi setiap pemimpin Kristen, tokoh yang menjadi figur pemimpin berhati hamba adalah Yairus.Penelitian ini menggunakan metode diskritif literatur, yaitu mempelajari tentang Pemimpin yang berhati hamba menurut Markus 5:21-43 Kesimpulan yang dapat disampaikan, pertama, kepemimpinan berhati hamba menjadi gaya hidup setiap pemimpin Kristen. Kedua, para pemimpin Kristen dapat mengimpartasikan teladan gaya pelayanannya sehinga berdampak pada karakter jemaat atau pelayanan Tuhan lainnya. Ketiga, dapat mendorong munculnya pemimpin-pemimpin baru yang memiliki hati hamba.